Crystalline Structure Analysis of Bamboo and Coconut Coir–Based Activated Carbon for Supercapacitor Electrode Applications - Heindrich Taunaumang; F. Tumimomor; A.M. Rampengan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Activated carbon has been developed for supercapacitor electrode material due to their high degree of micro porosity and large surface area. The carbon source, preparation conditions such as temperature and atmosphere, and preparation method strongly influence the crystalline structure and the properties of carbon materials. This article is focused on the crystalline structure analysis of bamboo and coconut coir activated carbon The bamboo and coconut coir carbon were fabricated by using pyrolysis method. The activated bamboo carbon and activated coconut coir carbon were produced using a chemical activation method where H3PO4 solution as activator agent. Characterization of the physical/crystalline structure of the bamboo carbon (BC), and coconut coir carbon (CCC) and bamboo activated carbon (BAC), coconut coir activated carbon (CCAC) was determined using XRD measurement. The XRD spectra of BC and BAC indicate that the percentage crystallinity are 29.1%, and 18.4% respectively. For CCC and CCAC the percentage crystallinity are 11.3% and 13.2%, respectively. The interlayer spacing (dhkl) for BC is 4.05 Angstrom, and for BAC is 3,79 Angstrom. The crystallite height (Lc) for BAC is 6.64 Angstrom and for BC is 21.56 Angstrom. The interlayer spacing (dhkl) for CCC and CCAC are the same 4.05 Angstrom. The crystallite height (Lc) for CCAC is 4.96 and for CCC is 2.83 Angstrom.